A COMPARITIVE STUDY OF DIFFERENT CARRIERS FOR SHELFLIFE OF PSEUDOMONAS FLUORESCENS - R. M. GADE; B. H. CHAITHANYA; K. C. KHURADE (The Bioscan, 2014)
Studies were carried out to evaluate different carriers for shelf life of Pseudomonas fluorescens stored at 25±20 C over a storage period of 6 months. The population dynamics was recorded at monthly intervals. The population of P. fluorescens was increased significantly in all carriers i.e Talc, Spent mushroom substrate (SMS) a waste product of mushroom industry, Lignite, Charcoal, Farm yard manure (FYM) and Flyash up to 60 days storage and there was slow decline in number of viable propagules after 60 days of storage.Spent mushroom substrate (78× 108 cfu/g) and fly ash (53.67× 108 cfu/g) maintained viable population count at 90 days of storage.This population was very close to the population recorded in carrier’s viz., Talc (86.33×108 cfu /g), Lignite (80×108 cfu /g) which were usually used in biofertilizer industry. Hence for short storage period, option of SMS and Fly ash can be used for developing commercial formulations of P. fluorescens. Talc was found to be the best carrier material that maintained better population of the P. fluorescens (18 ×108 cfu/g) till the end of storage period.